Inexpensive Apparatus for High-Quality Imaging of Microbial Growth on Agar Plates - Smith, Parker; Schuster, Martin (Frontiers in Microbiology, 2021)
The ability to capture images of results or processes is an important tool in the biologist’s tool kit. In microbiology, capturing high-quality images of microbial growth on agar plates is difficult due to the reflective surface of the plates and limitations in common photography techniques. Equipment has been developed to overcome these challenges, but acquisition costs are high. We have developed an inexpensive and efficient apparatus for high-quality imaging of microbial colonies. The imaging box, as we have named the apparatus, is designed to eliminate glare and reduce reflections on the surface of the plate while providing uniform, diffuse light from all sides. The imaging box was used to capture hundreds of images in research and teaching lab settings.